Estimation of arboreal lichen biomass available to woodland caribou in Hudson Bay lowland black spruce sites - Proceviat, Sarah K.; Mallory, Frank F.; Rettie, W. James (Rangifer, 2003)
An arboreal lichen index to be utilized in assessing woodland caribou habitat throughout northeastern Ontario was developed. The "index" was comprised of 5 classes, which differentiated arboreal lichen biomass on black spruce trees, ranging from maximal quantities of arboreal lichen (class 5) to minimal amounts of arboreal lichen (class 1). This arboreal lichen index was subsequently used to estimate the biomass of arboreal lichen available to woodland caribou on lowland black spruce sites ranging in age from 1 year to 150 years post-harvest. A total of 39 sites were assessed and significant differences in arboreal lichen biomass were found, with a positive linear relationship between arboreal lichen biomass and forest age. It is proposed that the index be utilized by government and industry as a means of assessing the suitability of lowland black spruce habitat for woodland caribou in this region.